2021
DOI: 10.1111/ejss.13155
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cations at the illite–water interface and its effect on intrinsic potassium ions

Abstract: Na + , K + , Cs + and Ca 2+ are common exogenous cations that could be introduced into soils either via long-term tillage with inorganic fertilizers or the leakage of nuclear waste. However, the manner in which they co-adsorb and compete with the intrinsic potassium ions in illite, the response of intrinsic potassium (K 0+ ), as well as the underlying mechanisms of these interactions, remain unclear. These aspects were explored using molecular dynamics simulations based on a series of concentrations. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Other studies have demonstrated that Na + ions preferred to anchor at the siloxane ring of illite which also contains a large number of negative charges. 67 An obvious sharp peak was also observed at each pH value in the RDFs of Na–OW (Fig. 7c), at a distance of 0.24 nm, due to the strong hydration energy of Na + .…”
Section: Resultsmentioning
confidence: 84%
“…Other studies have demonstrated that Na + ions preferred to anchor at the siloxane ring of illite which also contains a large number of negative charges. 67 An obvious sharp peak was also observed at each pH value in the RDFs of Na–OW (Fig. 7c), at a distance of 0.24 nm, due to the strong hydration energy of Na + .…”
Section: Resultsmentioning
confidence: 84%
“…Illite, a common layered aluminosilicate with a nanopore structure, is distributed widely in soils and has significant environmental implications (Yesilbas et al , 2019; Li et al , 2022). Its limited interlayer space leads to its large SSA, large CEC and good adsorption performance.…”
Section: Clay Minerals Regulate the Structure And Function Of Soilmentioning
confidence: 99%